Epic Formulas with a Matrix Construction: from Stability in Structure to Reference in Consciousness (Image of a Hero in the Yakut Olonkho) - Yu. P. Borisov (Научный диалог, 2020)
The complex processes involved in the generation of the image of the hero by the narrator and the perception of this image by the epic audience are studied. A comprehensive analysis of epic formulas with a matrix construction is carried out in order to identify their reference models. The novelty of the work lies in the fact that for the first time the problems of human speech-thinking activity on the basis of the epic formulas of the Yakut olonkho are considered. As a result of the research, the author comes to the conclusion that when revealing the image of the hero, the narrator uses the parallels as a referent: property of the material / property of the image. It is noted that, in turn, the recipients decipher these constructions thanks to the background knowledge about the referent, in particular, about the property of the described material, which is mentally brought under the image of a hero. According to the author, the very structure of the organization of matrix structures does not allow the olonkhosut to completely replace the components that form the referent. Moreover, it is stated that the structure of the analyzed constructions ignores even gender differences in describing the image of heroic women. It is pointed out that the described processes, when the narrator recites certain analyzed epic formulas, occur in a very short time.